A Novel De Novo Variant in DYNC1H1 Causes Spinal Muscular Atrophy Lower Extremity Predominant in Identical Twins: A Case Report. (22nd July 2021) - Derksen, Alexa; Mirchi, Amytice; Tran, Luan T.; Cao-Lei, Lei; Oskoui, Maryam; Srour, Myriam; Poulin, Chantal; ,; Bernard, Geneviève
Mutations in DYNC1H1 have been shown to cause spinal muscular atrophy lower extremity predominant type 1 (SMALED1), an autosomal dominant genetic neuromuscular disorder characterized by degeneration of spinal cord motor neurons resulting in muscle weakness. Here, we describe monozygotic twins, one with a more severe upper motor neuron phenotype as a result of a suspected perinatal hypoxic-ischemic event and the other presenting a typical lower motor neuron phenotype. Using exome sequencing, we identified the novel de novo variant c.752G>T; p.Arg251Leu in DYNC1H1 . We thereby add this variant to the growing list of mutations in DYNC1H1 that cause SMALED1.